Social news, public spaces user online communicative behavior on virtual platforms employed by and for news - Batu, Alyssa Navarro
User comments are a key element of social news public spaces. In verbal and non-verbal forms, comments on below-the-line spaces of virtual platforms enable communication and interaction. Subsequently, communicative behavior which may vary per platform may be inferred from these texts. With each platform structured differently by affordances and discourse architecture, differences in communicative behavior may also be observed. This study then examines how the virtual platforms for online news, Facebook and websites, determine online communicative behavior, particularly in terms of verbal communication (VC) and non-verbal communication (NVC) features, and the level of interaction and disinhibition. With Speech Act Theory and Affordance Perspective comprising the theoretical framework, content analysis was performed on 74,460 comments. The speech act category Representation and Act Claim predominantly characterized the comments. The co-existence of NVC with VC was observed in only 12.8% of comments, with Emoji/Emoticon most predominant. While more user-to-content interaction was generally observed, hard news items on websites, particularly those regarding politics, were characterized by more user-to-user interaction. Consistent with literature, more impoliteness/incivility were observed on websites than on Facebook, and in hard news (i.e. politics) than in soft news.